2017
DOI: 10.1136/jim-2017-000449
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Efficacy Examination of Alvimopan for the Prevention of Postoperative Ileus

Abstract: Opioid analgesics exacerbate ileus through peripheral μ-opioid receptor action. Alvimopan, a μ-opioid receptor antagonist, has been proposed to alleviate postoperative ileus, leading to decreased time to return of gastrointestinal function and hospital discharge. As opioid-induced motility issues are only one factor affecting postoperative ileus, continued examination of the cost of the use and efficacy of the drug is needed. Data for this study were collected retrospectively from the charts of 55 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In a recent small retrospective analysis of alvimopan (n = 55) and matched controls (n = 58), the authors found no significant difference in length of hospital stay (4.6 vs 4.8 days; P = 0.72) or mean time to return to bowel function (68.5 vs 67.3 h; P = 0.83). 38 This study demonstrated that patients treated with alvimopan incurred significantly greater charges for medical and surgical supplies, pathology and cytology services, operating room charges, and therapy charges (P < 0.05). 38 However, these increases in costs were largely associated with surgical time and a shift in hospitalwide accelerated recovery efforts; they may also be due to differences in surgical complexity between groups.…”
Section: Alvimopan (Entereg®)mentioning
confidence: 74%
See 2 more Smart Citations
“…In a recent small retrospective analysis of alvimopan (n = 55) and matched controls (n = 58), the authors found no significant difference in length of hospital stay (4.6 vs 4.8 days; P = 0.72) or mean time to return to bowel function (68.5 vs 67.3 h; P = 0.83). 38 This study demonstrated that patients treated with alvimopan incurred significantly greater charges for medical and surgical supplies, pathology and cytology services, operating room charges, and therapy charges (P < 0.05). 38 However, these increases in costs were largely associated with surgical time and a shift in hospitalwide accelerated recovery efforts; they may also be due to differences in surgical complexity between groups.…”
Section: Alvimopan (Entereg®)mentioning
confidence: 74%
“…38 This study demonstrated that patients treated with alvimopan incurred significantly greater charges for medical and surgical supplies, pathology and cytology services, operating room charges, and therapy charges (P < 0.05). 38 However, these increases in costs were largely associated with surgical time and a shift in hospitalwide accelerated recovery efforts; they may also be due to differences in surgical complexity between groups. 38 Nevertheless, this suggests that patient selection is important in deciding who should receive ERAS interventions, including PAMORAs, such as alvimopan.…”
Section: Alvimopan (Entereg®)mentioning
confidence: 74%
See 1 more Smart Citation
“…[ 31 ] Alvimopan opioid receptor antagonists have recently been developed in the United States for POI, and have been introduced in China, and mainly used in cases of colon failure and to improve gastrointestinal transit function after surgery and decrease postoperative inflammation caused by an excess of nitric oxide that is released after muscular layer infiltration. [ 2 , 32 , 33 ] Therefore, when the local inflammatory response causes more intense symptoms of POI, alvimopan may no longer be an effective means to promote the recovery of POI. [ 33 , 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 32 , 33 ] Therefore, when the local inflammatory response causes more intense symptoms of POI, alvimopan may no longer be an effective means to promote the recovery of POI. [ 33 , 34 ]…”
Section: Introductionmentioning
confidence: 99%